The Impact of Earnings Information on Selected Foreign Securities Markets - Deakin, Edward B.; Smith, Charles H. (Journal of International Business Studies, 1978)
Accounting earnings data have been considered to possess information useful to investor decision making. If this is so, then stock prices may be expected to react to the release of earnings data under certain circumstances. This article extends the test of market price reaction to earnings announcements to the Toronto and Johannesburg stock exchanges. Unusual price activity at or near the time of the release of earnings information was found and considered to be a possible result of the earnings announcement.